Electrical Properties of Electric Vehicle Gear Oils - Ewa Barglik; Agnieszka Skibińska; Wojciech Krasodomski; Kornel Dybich; Dariusz Sacha (Energies)
This study compared the oxidation resistance of three commercial oils used in electric car transmissions. The tests were carried out on a stand equipped with a gear train in accordance with ASTM D5704. The changes in physicochemical and dielectric parameters as well as the degree of degradation were assessed by means of the FTIR spectral analysis method. Significant changes in physicochemical parameters were noticeable, including an increase in the acid number as well as an increase in kinematic viscosity at 40 °C and a decrease at 100 °C. The test results show that the oil dedicated to hybrid vehicles degraded the least, while the other oils, dedicated to electric vehicles, lost their lubricating properties to a significant extent. In addition, attention was paid to the abrasion generated during the operation of the gearbox, which has a fairly considerable impact on the change in the dielectric properties of the oils tested. In the future, more detailed research should be carried out on the effects of varying temperatures and of an electromagnetic field on the degradation of gear oils dedicated to EVs and to determine how their dielectric properties change.